2021
DOI: 10.1107/s2053230x21003150
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the GTP-binding protein-like domain of AGAP1

Abstract: AGAP1 is often considered to regulate membrane trafficking, protein transport and actin cytoskeleton dynamics. Recent studies have shown that aberrant expression of AGAP1 is associated with many diseases, including neurodevelopmental disorders and acute lymphoblastic leukemia. It has been proposed that the GTP-binding protein-like domain (GLD) is involved in the binding of cofactors and thus regulates the catalytic activity of AGAP1. To obtain a better understanding of the pathogenic mechanism underpinning AGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…AGAP1 is an inclusion‐related protein that activates the GTPase of ADP ribosylation factor in a phosphoinositol‐dependent manner, influencing the formation of the actin cytoskeleton. 41 Previous studies have reported that AGAP1 was highly expressed in IGH::DUX4 types of leukaemia. 2 CD371 is a protein associated with cell lectin CLEC12A expression, and studies have shown that CD371 is specifically highly expressed in IGH::DUX4 patients.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…AGAP1 is an inclusion‐related protein that activates the GTPase of ADP ribosylation factor in a phosphoinositol‐dependent manner, influencing the formation of the actin cytoskeleton. 41 Previous studies have reported that AGAP1 was highly expressed in IGH::DUX4 types of leukaemia. 2 CD371 is a protein associated with cell lectin CLEC12A expression, and studies have shown that CD371 is specifically highly expressed in IGH::DUX4 patients.…”
Section: Resultsmentioning
confidence: 98%
“…To investigate whether and how TCF12 facilitated IGH::DUX4‐mediated transcription, the abnormal transcriptional activation of IGH::DUX4 targeted genes such as AGAP1 , CLEC12A , ERG alt , CLEC12A alt and C6orf89 alt was measured by qRT‐PCR in leukaemia cell lines REH and NALM‐6. AGAP1 is an inclusion‐related protein that activates the GTPase of ADP ribosylation factor in a phosphoinositol‐dependent manner, influencing the formation of the actin cytoskeleton 41 . Previous studies have reported that AGAP1 was highly expressed in IGH::DUX4 types of leukaemia 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Among them, AGAP1 was widely recognized as a gene involved in the regulation of membrane transport and protein transport. Additionally, it has been linked to psychiatric disorders such as autism and schizophrenia ( 32 ). The NFI family is a crucial family of transcription factors involved in adenoviral DNA replication, which consists of 4 genes, including NFIA , NFIB , NFIC , and NFIX , in most vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together the data suggest the GAP domain is not sufficient for targeting AGAP2 to the phagocytic cup. Several reports suggest that the GLD domain binds GTP or other nucleotide triphosphates and that intra-molecular interactions with the GAP domain enhance its atypical GTPase activity [6,7,[79][80][81].…”
Section: Discussionmentioning
confidence: 99%